Corporate Tax Avoidance and Its Influencing Factors: The Roles of Transfer Pricing, Thin Capitalization, Profitability, Fixed Asset Intensity, and Foreign Ownership - Isti Mulyasari; W. Widyasari (Golden Ratio of Taxation Studies, 2026)
Taxes are a primary source of state revenue that plays a crucial role in financing national development. However, companies often implement various tax planning strategies to reduce their tax burden, one of which is tax avoidance. This study examines the effect of transfer pricing, thin capitalization, profitability, fixed asset intensity, and foreign ownership on tax avoidance among consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employs a quantitative research design using secondary data collected from the companies’ annual financial reports. The sample was selected through purposive sampling, resulting in 29 companies with a total of 116 firm-year observations. Panel data regression analysis was employed using the Common Effect Model (CEM) as the most appropriate estimation model. The empirical results reveal that profitability has a positive and statistically significant effect on tax avoidance, indicating that more profitable firms tend to engage in higher levels of tax avoidance. In contrast, foreign ownership has a negative and statistically significant effect on tax avoidance, suggesting that greater foreign ownership is associated with lower tax avoidance practices. Meanwhile, transfer pricing, thin capitalization, and fixed asset intensity exhibit no statistically significant effect on tax avoidance. These findings indicate that profitability and ownership structure are important determinants of corporate tax avoidance, whereas financing decisions, related-party transactions, and asset composition do not significantly influence tax avoidance in the observed companies. This study contributes to the tax avoidance literature by providing empirical evidence from the Indonesian consumer non-cyclicals sector and offers insights for policymakers and corporate management in developing more effective tax governance and regulatory policies.